Psychosocial functioning and self‐rated health in Japanese school‐aged children: A cross‐sectional study. (29th October 2012) - Okuda, Masayuki; Sekiya, Mari; Okuda, Yumi; Kunitsugu, Ichiro; Yoshitake, Norikazu; Hobara, Tatsuya
Abstract Emotional and behavioral disorders in children are school‐health concerns; however, Japanese screening tools for such disorders are not yet available. We examined the association between psychosocial functioning as measured by the Pediatric Symptom Checklist (PSC) and self‐rated health within school settings. A cross‐sectional study was conducted for 2513 fifth and eighth graders from all of the primary and secondary schools in Shunan City, Japan. The Japanese PSC had high internal consistency (Cronbach's α = 0.90) and a factor structure similar to that of the English PSC. When the cut‐off values were set to ≥ 28 and ≥ 17, 4–9% and 20–39% of our respondents, respectively, reported high PSC scores. A multiple ordinal logistic regression analysis showed that the odds ratio of a positive PSC score (≥ 28) for poorer self‐rated health among ratings of "very good, " "good, " "fair, " and "poor" was 3.5 (95% confidence interval = 2.6–4.8). There was a clear association between psychosocial dysfunction identified by a PSC score ≥ 28 and poor self‐rated health. We offer directions for further research on appropriate PSC cut‐off values with Japanese samples.